Implementasi Program Cara Budidaya Ikan yang Baik Bagi Masyarakat Pembudidaya Ikan di Kabupaten Bolaang Mongondow Timur - AYUNINGTYAS, WAHJOE DYAH; PRAKTINJO, MARIA HENY; PURWANTO, ANTONIUS (JURNAL ADMINISTRASI PUBLIK, 2018)
Abstract :Implementation Program Good Fish Cultivation (CBIB) is an activity that teaches about howto cultivate a good fish so as to produce good products. in East Bolaang Mongondow Regency is stillvery low level of knowledge about CBIB thus affecting freshwater fish production level. The researchobjectives are: To know and analyze the Implementation of CBIB Program for Fish CultivationSociety in East Bolaang Mongondow Regency This study employ a qualitative study method thatlocated in Community Seeds Unit and Group of Fish Farmers in East Bolaang Mongondow.This thesis research uses qualitative research method, with research location in communityseed unit (UPR) and Pokdakan (fish farmer group) in Bolaang Mongondow eastThe result of the research shows that the implementation of CBIB program in East BolaangMongondow Regency is not optimal yet. constraints such as, lack of CBIB Auditor in East BolaangMongondow Regency so lack of guidance and supervision. Constraints are also lack of humanresources that have the potential to become a CBIB auditor and also related to program budget, sothat CBIB Implementation can not be applied maximally.From the results of this study, it can be concluded that CBIB Implementation can not bedone well because it is influenced from 3 aspects: Organization aspect, Interpretation aspect, andaspect of Application. It is recommended that the East Bolaang Mongondow Regional Administratorshould make efforts to support the fulfillment of the needs of fish farmers in Bolaang MongondowTimur District in terms of organizational aspect, interpretation aspect, and application aspect so thatthe achievement of production and safety and quality can be improved.Keyword: implementation, good fish cultivation program, fish farmer community